Ontologi, Epistemologi, dan Aksiologi Kurikulum Pesantren Di MI Maarif NU Tunjungmuli 1 - Iik Nuralim; Abdul Wachid Bambang Suharto (UMSU, 2022)
In the era of globalization, education in Indonesia has experienced various problems, often infecting students. Immoral violations through social media and rampant bullying cases carried out by students have resulted in a crisis of character and morals of the nation's children so that the world of education is getting worse which results in a decline in public trust. The implementation of education with an integrated school model with pesantren is one answer to this problem. MI Ma'arif NU Tunjungmuli 1 is a Madrasah that applies two curricula in the learning process, namely the 2013 curriculum and the pesantren curriculum. This paper uses a descriptive qualitative research method to analyze the ontology, epistemology, and axiology of the Islamic boarding school curriculum at MI Ma'arif NU Tunjungmuli 1. The use of data is carried out using observation, interview, and documentation techniques. The subjects of this study were the Head of Madrasah Ibtidaiyah, Deputy Head of Madrasah, Waka Kurikukum, Board of teachers, and students of MI Ma'arif NU Tunjungmuli 1. The purpose of this study was to describe the ontology, epistemology and axiology of the curriculum of the MI Ma'arif NU Tunjungmuli Islamic boarding school 1. The research shows the results that the pesantren curriculum in the ontology perspective concerns the nature of the curriculum, pesantren, and the pesantren curriculum. In the epistemological review, it presents the method of implementing the pesantren curriculum. In the axiological review, it explores why the pesantren curriculum is applied and what is the purpose of the pesantren curriculum.